Comparative Analysis of Peptide Composition and Bioactivity of Different Collagen Hydrolysate Batches on Human Osteoarthritic Synoviocytes - Simons, Viktor S.; Lochnit, Guenter; Wilhelm, Jochen; Ishaque, Bernd; Rickert, Markus; Steinmeyer, Jürgen; Justus Liebig University Giessen (My University, 2018)
Collagen hydrolysates (CHs) are heterogeneous mixtures of collagen peptides that are often used as nutraceuticals for osteoarthritis (OA). In this study, we compared the peptide composition and pharmacological effects of three different CH preparations (CH-Alpha((R)), Peptan((R)) B 2000 and Mobiforte((R))) as well as their production batches. Our biochemical analysis using MALDI-TOF mass spectrometry and the ICPL-isotope labelling method revealed marked differences between different CH preparations and even between some production batches of the same preparation. We also investigated the pharmacological effects of these CHs on human fibroblast-like synoviocytes (FLS). No significant effects on cultured FLS could be demonstrated for either production batch of CH-Alpha((R)), Peptan((R)) B 2000, and Mobiforte((R)) analyzing a small number of pharmacological relevant targets. Thus, our study already shows for the first time that different production batches of the same CH preparation as well as different CH preparations can differ significantly in their peptide composition. In this line, further studies are also needed to verify equal pharmacological efficacy of CH batches on a much broader range of (patho)physiological relevant targets. If OA patients are to be offered a safe and effective nutraceutical a better knowledge about all potential effects as well as ensuring the same active-substance levels are a prerequisite.
Keywords: ddc:610